2000
DOI: 10.1139/e98-088
|View full text |Cite
|
Sign up to set email alerts
|

Teleseismic studies of the lithosphere below the Abitibi-Grenville Lithoprobe transect

Abstract: Abstract:In the past decade, the Abitibi-Grenville Lithoprobe transect has been the site of numerous geological and geophysical surveys oriented towards understanding the lithospheric evolution of the southeastern Superior and adjoining Grenville provinces. Among the different geophysical methods that have been employed, earthquake seismology provides the widest range of information on the deep structures of the upper mantle. This paper presents a review of studies, both complete and ongoing, involving telesei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Sixty kilometers SE of the GF, Moho depth increases to 41-44 km ( Figure 5), consistent with wide-angle Lithoprobe surveys [e.g., White et al, 2000;Winardhi and Mereu, 1997;Martignole and Calvert, 1996]. Two receiver function profiles also image a sudden ∼10 km Moho depression ∼50 km SE of the Grenville Front [Rondenay et al, 2000;Eaton et al, 2006]. Increased thickness beneath the sections of the failed Iapetan Ottawa-Bonnechere Graben is also noted in a previous seismic survey that crosscuts the graben [Green et al, 1988].…”
Section: Comparison With Previous Studiessupporting
confidence: 83%
“…Sixty kilometers SE of the GF, Moho depth increases to 41-44 km ( Figure 5), consistent with wide-angle Lithoprobe surveys [e.g., White et al, 2000;Winardhi and Mereu, 1997;Martignole and Calvert, 1996]. Two receiver function profiles also image a sudden ∼10 km Moho depression ∼50 km SE of the Grenville Front [Rondenay et al, 2000;Eaton et al, 2006]. Increased thickness beneath the sections of the failed Iapetan Ottawa-Bonnechere Graben is also noted in a previous seismic survey that crosscuts the graben [Green et al, 1988].…”
Section: Comparison With Previous Studiessupporting
confidence: 83%
“…[21] The four data sets (FedNor/CNSN, APT89, Abitibi, and TW$ST) do not overlap in time. Therefore their event [Silver and Kaneshima, 1993;Kay et al, 1999;Rondenay et al, 2000aRondenay et al, , 2000bEaton et al, 2004] are shown as gray arrows; black arrows are results for POLARIS, FedNor, and CNSN stations in this study. White triangles indicate stations with split times of 1 s or more.…”
Section: Traveltime Measurementsmentioning
confidence: 94%
“…Additionally, a shallower lithosphere underlain by hydrated asthenospheric melts beneath the Appalachians may also be contributing to the observed decrease in seismic velocity [e.g., Rychert et al, 2005]. [Sénéchal et al, 1996;Rondenay et al, 2000b;Eaton et al, 2004;Frederiksen et al, 2006;Darbyshire et al, 2015;Gilligan et al, 2016]. Arrows are the APM vectors in the no-net-rotation frame [DeMets et al, 2010] (dark blue) and in the hot spot frame [Gripp and Gordon, 2002] (light blue).…”
Section: Velocity Decrease Beneath Proterozoic and Younger Provincesmentioning
confidence: 99%